Foot and ankle injuries in competitive senior divers - Mizel, M. S.; Marymount, J. V.; Decker, J. E.; Trepman, E.; Rubin, B. D. (BioMechanics Journal, 1996)
A specific sequence of movements is required to perform a dive in which normal function of the foot and ankle is crucial. Injury to either can render the diver unable to perform a specific part of the dive, limiting both dive selection and performance.